MENYOAL PENELITIAN FENOMENOLOGIS : Kerangka Filosofis, Konsepsi dan Desain - Puad Hasan (Edusifa: Jurnal Pendidikan Islam, 2025)
in the beginning, phenomenology was a philosophy popularized by Edmund Husserl. Phenomenology essentially teaches people to interact and learn more about phenomena so that observers can capture their meaning and essence. Phenomenology is currently being developed as a fundamental research method based on understanding the uniqueness of people and their subjective experiences. Phenomena experienced by people consciously are analyzed using two descriptions: textual descriptions and biblical descriptions. This article attempts to explore how phenomenological research projects are created.